Predicting preschool moral development with school climate: Fuzzy Delphi approach - Abdul Halim Masnan; Nurul Khairani Ismail; Wayhidah Usop; Diani Mardiana Mat Zain (International Journal of Evaluation and Research in Education (IJERE), 2024)
Education is vital for a person’s development, especially from an Islamic perspective, where the first goal is to foster a servant attitude, talent, personality, and outlook on life. Preschool education is crucial in nurturing a child's nature, emotions, and cognitive and social skills in the first five years. However, the significance of a good school environment, particularly in moral formation, varies among institutions. Therefore, this article aims to build consensus among experts on the role of school environment and classroom management in preschoolers’ moral development. Eleven-panel members validated the survey instrument with items and analyzed it using the Fuzzy Delphi method (FDM). According to the study, the experts agree that the physical school environment and classroom management are essential for promoting healthy moral development. Expert consensus was obtained on 19 out of 20 items in the physical school environment and classroom management dimension with an expert agreement level greater than 75% with an average (d) value less than 0.2. The undeniable consensus is that the school environment and classroom management play a crucial role in fostering the moral development of preschool children.